PENGEMBANGAN SISTEM MANAJEMEN MUTU SEBAGAI ALAT KONTROL PRODUKTIVITAS KINERJA PEKERJA STRUKTUR BERBASIS INEFFECTIVE WORK (STUDI KASUS : PROYEK PADINA SOHO & RESIDENCE) - Redaksi Tim Jurnal (FORUM MEKANIKA, 2018)
This study aims to analyze the productivity of structural workers in the Padina Soho & Residence Project and make the Quality Management System based on ineffective work as a tool to control the productivity of structural workers' performance. Data collection techniques are carried out by field observations and interviews. The method used to measure the level of productivity is work sampling. The productivity measure obtained from this analysis is the labor utilization rate (LUR). In this study there are three types of structural work observed, formwork, reinforcement work, and casting work. Furthermore, the development of the Quality Management System is based on ineffective work as a tool to control the productivity of structural workers' performance.